Repeat Head CT for Neurologically Stable Patients With Mild Traumatic Subarachnoid Hemorrhage During Interfacility Transfer and Follow-Up Does Not Alter Patient Care. Issue 3 (August 2021) - Pillenahalli Maheshwarappa, Ravishankar; Valand, Hardik A.; Locke, Thomas; Soni, Neetu; Bathla, Girish
Purpose: To evaluate the impact of repeat head computed tomography (CT) during (1) interfacility transfer and (2) inpatient and/or outpatient follow-up on management, cost-effectiveness, and radiation dose in neurologically stable patients with mild traumatic subarachnoid hemorrhage (tSAH). Material and Methods: This is a single-center retrospective study evaluating patients with mild tSAH presenting between January 2017 and July 2019. A total of 101 and 140 patients met the eligibility criteria for the first and second subgroups, respectively. Common inclusion criteria were isolated mild tSAH, Glasgow Coma Scale between 13 and 15, and neurological stability. Additional inclusion criteria for the first subgroup were availability of brain imaging at the outside institution prior to transfer and the second subgroup was the availability of follow-up imaging. Results: In the first subgroup, 76.20% of patients had stable SAH, 18.80% had reduced SAH, while 5% had an interval increase in SAH. None required any surgical intervention. Additional per-patient mean radiation exposure was 1.77 ± 0.26 mSv. In the second subgroup, all 140 patients had complete resolution of tSAH. One patient had a new tiny subdural hemorrhage, which subsequently resolved on follow-up. The additional mean radiation exposure was 2.47 ± 1.29 mSv. A total of 256 avoidable CT scans were performed resulting in excess health care costs of about US$531 696. Conclusion: In neurologically stable isolated tSAH patients, repeat brain imaging during interfacility transfer and inpatient and/or outpatient follow-up do not alter patient management despite increased health care costs and radiation burden.